Menilai kinerja keuangan pada bank Panin Dubai Syariah: Pendekatan analisis rasio dan common-size - nisa, fitria izzatun; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
The purpose of this study is to analyze the financial performance of PT Bank Panin Dubai Syariah during the period 2019 to 2023 using a ratio and common-size analysis approach. The Islamic banking sector in Indonesia has shown significant growth, despite facing various challenges due to the impact of the pandemic. Through ratio analysis, fluctuations in indicators such as ROA, ROE, NPM, and DER can be seen, reflecting the extent of banks' resilience in the face of uncertain economic pressures. In addition, a common-size analysis revealed a change in the bank's strategy which is now more focused on the growth of third-party funds. The results of this study show that despite positive signs of recovery in 2022 and 2023, banks still need to strengthen their capital structure and improve operational efficiency to support sustainable growth. The proposed strategic suggestions include diversifying revenue sources as well as more effective debt management to improve the bank's overall performance.